Resilience rising: Redefining livelihood systems in disaster-prone rural communities - Reza Amarta Prayoga; Eko Wahyono; Nuzul Solekhah; Fatwa Nurul Hakim; Siti Fatimah; Lis Purbandini; Djoko Puguh Wibowo; Rachmini Saparita (Progress in Disaster Science)
This study emphasizes the need for a critical review of existing literature to identify the enablers and barriers to social modeling. Rather than solely focusing on vulnerability, it seeks to deconstruct and redefine resilience, particularly in the context of livelihood systems within communities that have been underexplored in current research. Through a qualitative approach, the study combines critical and constructivist paradigms to develop social modeling that enhances the resilience of disaster-prone communities via their livelihood systems. The goal is to create an innovative, participatory, and sustainable model for rural community livelihoods that can withstand challenges. Central to this model is the accumulation of both capital and social capital. The study offers strategic and practical recommendations for stakeholders and communities in disaster-prone areas to rebuild more robust livelihood systems by harnessing ecological, social, economic, and cultural potentials. It has significant implications for the analytical framework of community livelihood systems and the strategic and operational planning needed to address livelihoods in disaster-affected areas. Social modeling is a critical strategy for planning and implementing social protection and economic mitigation in such communities.